Gendered fields: Women, men, and ethnography - Karim, Wazir-Jahan Begum; Bell, Diane; Caplan, Pat (Routledge, 2013)
Examines and explores the progress of feminist anthropology, the gendered nature of fieldwork itself, and the articulation of gender with other aspects of the persona of the ethnographer.
Keywords: anthropologie; approches et analyses; discipline; ethnographie; genre; outils; ouvrages de références; point de vue situé; sciences humaines

Le standpoint theory : en faveur d'une nouvelle méthode épistémologique - Larivée, Christian (Ithaque, 2013)
Cet article est avant tout une présentation générale du standpoint theory mais vise tout particulièrement à souligner la relation épistémologique qui unit cette théorie féministe à la théorie marxiste. Ainsi il y sera démontré que l’expérience de l’oppression, et donc de la souffrance qui l’accompagne, est en mesure de représenter un avantage épistémique que les groupes subissant l’oppression peuvent tourner à leur avantage. Il sera donc question d’un nouveau type d’objectivité délaissant le concept de neutralité en faveur d’une subjectivité pleinement assumée
Keywords: approches et analyses; cours; discipline; phi4336; philosophie politique; point de vue situé; premier cycle; ressource en ligne; sciences humaines; sofia; thématiques; épistémologie; épistémologies féministes

Cross-dressing to backbeats: An exploration of the practices, wo/men producers, and history of electroclash - Madden, David (Université Concordia, 2013)
This research-creation dissertation focuses on the emergence of electroclash as a dominant form of electronic dance music in the late 1990s and early 2000s. Electroclash combines the extended pulsing sections of techno, house and other dance musics with the trashier energy of rock and new wave. The genre signals an attempt to reinvigorate dance music with a sense of sexuality, personality and irony. Electroclash also emphasizes, rather than hides, the European, trashy elements of electronic dance music. This project addresses the following questions: what is distinct about the genre and its related practices, both in and out of the studio? Why do rock and electro come together at this point and in this way? Why is electroclash affectively powerful for musicians, audiences and listeners? And, what does the genre portend in terms of our understandings of the politics of electronic music? The coming together of rock and electro is examined vis-à-vis the ongoing changing sociality of music production/distribution and the changing role of the producer. Numerous women, whether as solo producers or in the context of collaborative groups, significantly contributed to shaping the aesthetics and production practices of electroclash, an anomaly in the history of popular music and electronic music where the role of the producer has typically been associated with men. These changes are discussed in relation to the way key electroclash producers often used a hybrid approach to production involving the integration of new(er) technologies, such as laptops containing various audio production software with older, inexpensive keyboards, microphones, samplers and drum machines to achieve the ironic backbeat laden hybrid electro-rock sound.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; DIG; amériques; approches et analyses; communication; discipline; femmes* artistes; genre; historiographie; montréal; musique; mémoires/thèses; philosophie; point de vue situé; périodes historiques; recherche-création; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail

Le travail social entre émancipation et normalisation : une voie étroite pour les approches féministes - Modak, Marianne; Martin, Hélène; Keller, Véréna (Nouvelles Questions Feministes, 2013)
Édito
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem7000; féminisme matérialiste; histoire et politique; justice sociale; point de vue situé; pratiques féministes; rapports sociaux de sexe; sciences humaines; thématiques; théorie critique; travail social; émancipation

Towards an Australian Indigenous Women's Standpoint Theory - Moreton-Robinson, Aileen (Australian feminist studies, 2013)
In this article I outline an Australian Indigenous women's standpoint theory. I argue that an Indigenous women's standpoint generates problematics informed by our knowledges and experiences. Acknowledging that Indigenous women's individual experiences will differ due to intersecting oppressions produced under social, political, historical and material conditions that we share consciously or unconsciously. These conditions and the sets of complex relations that discursively constitute us in the everyday are also complicated by our respective cultural differences and the simultaneity of our compliance and resistance as Indigenous sovereign female subjects.
Keywords: approches et analyses; australie; cours; droits des femmes*; féminisme autochtone; histoire et politique; intersectionnalité; point de vue situé; pol4212; premier cycle; ressource en ligne; régions géographiques; thématiques